Gonadotrophin‐releasing hormone analogue or dienogest plus estradiol valerate to prevent pain recurrence after laparoscopic surgery for endometriosis: a multi‐center randomized trial. (29th March 2015) - Granese, Roberta; Perino, Antonino; Calagna, Gloria; Saitta, Salvatore; De Franciscis, Pasquale; Colacurci, Nicola; Triolo, Onofrio; Cucinella, Gaspare
<x xml:space="preserve">Abstract</x> Objectives To evaluate the efficacy of dienogest + estradiol valerate (E2V) and gonadotrophin‐releasing hormone analogue (GnRH‐a) in reducing recurrence of pain in patients with chronic pelvic pain due to laparoscopically diagnosed and treated endometriosis. Design Multi‐center, prospective, randomized study. Setting Three university departments of obstetrics and gynecology in Italy. Population Seventy‐eight women who underwent laparoscopic surgery for endometriosis combined with chronic pelvic pain. Methods Post‐operative administration of dienogest + E2V for 9 months (group 1) or GnRH‐a monthly for 6 months (group 2). Main outcome measures A visual analogue scale was used to test intensity of pain before laparoscopic surgery at 3, 6 and 9 months of follow up. A questionnaire to investigate quality of life was administered before surgery and at 9 months of follow up. Results The visual analogue scale score did not show any significant differences between the two groups (p = 0.417). The questionnaire showed an increase of scores for all women compared with pre‐surgery values, demonstrating a marked improvement in quality of life and health‐related satisfaction with both treatments. No significant differences were found between the groups. The rate of apparent endometriosis recurrence was 10.8% in group 1 and 13.7% in group 2 (p = 0.962). Conclusion Both therapies seemed equally efficacious in preventing endometriosis‐related chronic pelvic pain recurrence in the first 9 months of follow‐up.